Neuromodulação, atividade neuronal e respostas psicofisiológicas durante exercício físico - Agrícola, Pedro Moraes Dutra (2015)
Introduction: It is known that the prefrontal cortex plays an important role in the reward system, and the insular cortex aware information coming from the body condition on feelings. Therefore, modulation of these regions allows changes in the psychophysiological responses or behavior in a given situation, such as in physical exercise. Objective: To test the effect of neuromodulation on cerebral hemodynamics, perceptual and affective responses during exercise. Methods: Fourteen healthy men were assessed in five sessions. The first session was held the maximum incremental test on a cycle ergometer. The other sessions consisted of applied transcranial direct current stimulation (tDCS) in four diferent and randomized conditions, followed by thirty minutes of exercise at 90% of the ventilatory threshold. Cerebral oxygenation in the prefrontal cortex, perceived exertion and affect were measured. Results: The two-way ANOVA showed a decrease of affect throughout the exercise time (p<0.03) in all conditions except tDCS stimulation of the prefrontal cortex (p> 0.7). In addition, stimulation of the prefrontal cortex causes differences in the stretch of the slope in the second half of the exercise (p<0,05), showing that condition sustained affect behavior. Cerebral hemodynamics responses was similar between the conditions of tDCS (p≥0,3). However, the tDCS applied on the prefrontal cortex generated equality between the left hemisphere (Detector B) and the right hemisphere (Detector A), after tDCS (P = 1.00) and during exercise (p≥0,3), which did not occur in other conditions where the left hemisphere was greater than right (p<0.001). Conclusion: We conclude that the TDCs on the prefrontal cortex sustained the responses of affect favorably modifying its behavior during exercise, due to the change in neuronal activity pattern in the ventromedial prefrontal cortex. Increased activity in the ventral areas is associated with increased activity in the reward system, which in turn modulates emotional and perceptual aspects.